CAREER INFORMATION SERVICES TO INCREASE THE STABILITY OF STUDENTS' FUTURE STUDY SELECTION - Amin Subekti; Edi Perwanta (International Journal Multidisciplinary Science, 2024)
The objective of this research was to assess the effectiveness of career information services in enhancing the decisiveness of eighth-grade students at SMP Negeri 3 Sewon in choosing further studies. The research addressed the problem of indecisiveness among students in selecting their future education. A quantitative pre-test and post-test method was used, with 10 students identified in the low and very low categories based on their initial decisiveness. The treatment consisted of career information services delivered through lectures, discussions, and slide presentations. The research process followed several stages: an initial introduction, an explanation of the service, and interactive self-awareness games. This was followed by delivering career information through PowerPoint slides, a lecture, a Q&A session, and homework assignments. Finally, post-test assessments and feedback were collected to evaluate the effectiveness of the services provided. The results showed significant improvement in students' decisiveness after the treatment. Pre-test scores averaged 78.3, while post-test scores increased to 112.7, with a gain score of 0.37 (moderate effectiveness, 62.6%). The Wilcoxon signed rank test indicated a statistically significant difference (Z = 2.807, p = 0.005), confirming that the intervention was effective. In conclusion, career information services were found to be an effective method for improving students' decisiveness in selecting further studies. This is consistent with previous studies, which demonstrated the role of career guidance in reducing uncertainty and supporting educational planning. The innovation of this research lies in the use of interactive and engaging media. It is recommended that career information services be expanded to help more students in their educational decisions.